The development of bookcreator as a learning innovation for instilling character values in early childhood education - Kurnia Jayadinata, Asep; Ardiyanti, Dhea; Nikawanti, Gia Nikawanti; Justicia, Risty; Nur Adliyani, Amanda; Rizky Febriani, Alya (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Enhancing character values during early childhood is a crucial component of implementing the Merdeka Curriculum and requires the support of engaging and interactive digital learning media. In the context of rapid technological development, educators are encouraged to integrate digital innovations that can meaningfully support character education while maintaining a child-friendly learning environment. Objective: This study aims to develop Book Creator–based learning media to strengthen character values namely honesty, responsibility, empathy, and cooperation in early childhood as an effort to create a joyful and meaningful learning environment. Method: This study employed a Research and Development (R&D) approach using the ADDIE model, involving early childhood teachers and preschool children in Purwakarta Regency, Indonesia. Data were collected through observation, interviews, questionnaires, and documentation, and were analyzed using descriptive, quantitative, and qualitative techniques. Results: The findings indicate that the Book Creator media, consisting of six interactive stories, achieved a validity score of 92% from media experts and 100% from content experts, categorizing it as highly valid. Practicality testing conducted by teachers yielded a 100% score, indicating that the media is very practical, engaging, and easy to use. Furthermore, the media was proven effective in enhancing children’s understanding of character values and demonstrated uniqueness as an interactive thematic storytelling medium specifically designed for early childhood character education. Conclusion: With high levels of validity, practicality, and effectiveness, the developed Book Creator media shows strong potential for broader implementation as an adaptive digital learning innovation to support character education for young children in the technological era.